Civilization approach in sportsology - Vinokurova U.A.; Alekseev V.N.; Alekseeva G.G. (Theory and Practice of Physical Culture, 2024)
Objective of the study of sportology through a civilizational approach based on the analysis of the effective practices of outstanding coaches such as Dmitry Petrovich Korkin. Methods and structure of the study. The main content of the study is the indigenous methodology of Indigenous Methodology, according to which athletes are assigned additional moral responsibilities to preserve the spiritual freedom, ethical ideals and spiritual values of their people, absorbed from birth and embodied in the cultural codes of socialization. Results and conclusions. The civilizational approach, in contrast to the universalism of the formational method, introduces methodological aspects of the institutionalization of sports into sportology: national characteristics of physical culture and ethnic sports, international trends in civilizational and country dimensions, the impact of global climate change on the interaction of civilizations in the South-North direction, equality of peoples and civilizations , an appeal to the sporting potential of Eurasia.